ANALISIS PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA CV. MITRA SETIA AGUNG KECAMATAN KOLOR KABUPATEN SUMENEP - Hairul Fadli; Budi Wahono; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study was conducted to determine whether there is a relationshipbetween the variables studied and then analyzed by hypothesis. This type ofresearch is a type of explanatory research where the study explains therelationship between the variables. The result of this research can be observedthat jointly motivation variable (X1), perception (X2), personality (X3), attitude(X4) have a significant influence simultaneously to Honda brand motorcyclepurchase decision (Y). And the perception variable (X2) has a dominant influenceon the purchasing decision of Honda (Y) Brand motorcycle.Keywords: Motivation, perception, personality, attitudes and purchasingdecisions